1979
DOI: 10.1042/bj1770081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of organic phosphorus covalently bound to collagen and non-collagenous proteins of chicken-bone matrix. The presence of O-phosphoserine and O-phosphothreonine in non-collagenous proteins, and their absence from phosphorylated collagen

Abstract: Non-collagenous phosphoproteins, almost all of which can be extracted in EDTA at neutral pH in the presence of proteinase inhibitors, are identified in the matrix of chicken bone, and are therefore not covalently bound to collagen. Similarly, all the peptides containing y-carboxyglutamic acid are present in the EDTA extract and none in the insoluble residue, confirming that none is covalently linked to chicken bone collagen. However, organic phosphorus is also found to be present in chicken bone collagen, prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…We believe it may be concluded that the "P-labeled components visualized in this study by radioautography represent principally the phosphoproteins isolated and characterized previously (14,(21)(22)(23). The localization of silver grains over endoplasmic reticulum and Golgi apparatus of osteoblasts provides further strong evidence that the phosphoproteins are synthesized principally by these cells, a conclusion consistent with the results recently obtained in cell culture by Gotoh et al (15).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We believe it may be concluded that the "P-labeled components visualized in this study by radioautography represent principally the phosphoproteins isolated and characterized previously (14,(21)(22)(23). The localization of silver grains over endoplasmic reticulum and Golgi apparatus of osteoblasts provides further strong evidence that the phosphoproteins are synthesized principally by these cells, a conclusion consistent with the results recently obtained in cell culture by Gotoh et al (15).…”
Section: Discussionsupporting
confidence: 80%
“…The "P-labeled phosphoprotein(s) identified in the present experiments are, like those isolated and characterized from whole postnatal chick bone (21) and those synthesized in organ and cell culture (14,15) in EDTA, are nondiffusible and contain both Ser(P) and Thr(P) . We believe it may be concluded that the "P-labeled components visualized in this study by radioautography represent principally the phosphoproteins isolated and characterized previously (14,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The phosphate content was analyzed chromatographically on a Beckman 121M amino acid analyzer as phosphoserine and phosphothreonine after hydrolysis in 4 M HCl for 6 hr at 105°C as described by Cohen-Solal et al (18) in the laboratory of Melvin Glimcher (Childrens Hospital Medical Center).…”
Section: Methodsmentioning
confidence: 99%
“…Very few bona fide examples of glutamyl phosphates in eukaryotes have been described. The best documented case is that of the ␣2 chains of type I chicken bone collagen (46), where 4 -5 atoms of organic phosphorus/mol of collagen were found in the absence of phosphorylated hydroxyamino acids, phosphoamidated amino acids, or phosphorylated sugars (47). These glutamyl phosphate groups, which survived in part during the several hours needed for purification of the protein, were later localized to a specific peptide (48).…”
mentioning
confidence: 99%